Mineralogical and Geochemical Control of Altered Andesitic Tuff upon Debris Slide Occurences at Pelangan Area, Southern Mountain of Lombok Island, Indonesia - Dwi Winarti; Dwikorita Karnawati; Hary Christady Hardiyatmo; Srijono Srijono (Geological Engineering Department Universitas Gadjah Mada, 2016)
Debris slides were recently found in the Pelangan area at Southern Mountain of Lombok Island, Indonesia. Pelangan is well known as the gold mineralization and hydrothermal alteration area. This study is aimed to identify the mineralogy and geochemistry of altered andesitic tuff that controlled slope instability and induced debris slides. For this purpose, it is necessary to prepare the field observation and laboratory analyses. Landslide inventory reveals that the Pelangan debris slides mostly occur in altered andesitic tuff. Based on the outcrop observations in the field, andesitic tuff found around the Pelangan debris slides have been altered in general. The strong intensity of alteration developed by hydrothermal alteration in this study area produces large amount of clay minerals especially montmorillonite, kaolinite, and illite. The abundance of those clay minerals reflect the intermediate argillic alteration. Montmorillonite is a type of clay mineral that easily swells at wet condition and easily shrinkages at dry condition. Swelling of clay mineral destroys intersheet and interlayer bonds, and reduces shear strength. The presence of clay minerals in the altered andesitic tuff of intermediate argillic zone can be considered as one of the factors that induced to the Pelangan debris slides. Further studies on geotechnical and slope stability analysis of the landslide area are crucial to be done for better understanding of the characteristics of the altered rocks inducing hazardous landslides.